Genome-Wide Analysis and Expression Profiling of the SUC and SWEET Gene Families of Sucrose Transporters in Oilseed Rape (Brassica napus L.) - Jian, Hongju; Lu, Kun; Yang, Bo; Wang, Tengyue; Zhang, Li; Zhang, Aoxiang; Wang, Jia; Liu, Liezhao; Qu, Cunmin; Li, Jiana (Frontiers in Plant Science, 2016)
Sucrose is the principal transported product of photosynthesis from source leaves to sink organs. SUTs/SUCs (sucrose transporters or sucrose carriers) and SWEETs (Sugars Will Eventually be Exported Transporters) play significant central roles in phloem loading and unloading. SUTs/SUCs and SWEETs are key players in sucrose translocation and are associated with crop yields. The SUT/SUC and SWEET genes have been characterized in several plant species, but a comprehensive analysis of these two gene families in oilseed rape has not yet been reported. In our study, 22 and 68 members of the SUT/SUCs and SWEET gene families, respectively, were identified in the oilseed rape (Brassica napus) genome through homology searches. An analysis of the chromosomal distribution, phylogenetic relationships, gene structures, motifs and the cis-acting regulatory elements in the promoters of BnSUC and BnSWEET genes were analysed. Furthermore, we examined the expression of the 18 BnSUC and 16 BnSWEET genes in different tissues of ‘ZS11’ and the expression of 9 BnSUC and 7 BnSWEET genes in ‘ZS11’ under various conditions, including biotic stress (Sclerotinia sclerotiorum), abiotic stresses (drought, salt and heat), and hormone treatments (abscisic acid, auxin, cytokinin, brassinolide, gibberellin and salicylic acid). In conclusion, our study provides the first comprehensive analysis of the oilseed rape SUC and SWEET gene families. Information regarding the phylogenetic relationships, gene structure and expression profiles of the SUC and SWEET genes in the different tissues of oilseed rape helps to identify candidates with potential roles in specific developmental processes. Our study advances our understanding of the important roles of sucrose transport in oilseed rape.